2018
DOI: 10.1108/ssmt-10-2017-0038
|View full text |Cite
|
Sign up to set email alerts
|

Morphology transformation on Cu3Sn grains during the formation of full Cu3Sn solder joints in electronic packaging

Abstract: Purpose This paper aims to analyze the morphology transformation on the Cu3Sn grains during the formation of full Cu3Sn solder joints in electronic packaging. Design/methodology/approach Because of the infeasibility of analyzing the morphology transformation intuitively, a novel equivalent method is used. The morphology transformation on the Cu3Sn grains, during the formation of full Cu3Sn solder joints, is regarded as equivalent to the morphology transformation on the Cu3Sn grains derived from the Cu/Sn str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…This was corresponding to the observation from the cross-sectional fracture morphology [Figure 11(e)]. It was said that the Cu 3 Sn grains presented coarse columnar shape when the full Cu 3 Sn joints were formed (Yao et al , 2018). From Figure 12(h), it could be also confirmed that the broken Cu 3 Sn grains were the coarse columnar grains which had experienced the transgranular fracture.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…This was corresponding to the observation from the cross-sectional fracture morphology [Figure 11(e)]. It was said that the Cu 3 Sn grains presented coarse columnar shape when the full Cu 3 Sn joints were formed (Yao et al , 2018). From Figure 12(h), it could be also confirmed that the broken Cu 3 Sn grains were the coarse columnar grains which had experienced the transgranular fracture.…”
Section: Resultssupporting
confidence: 80%
“…According to the EDS result [Figure 12(i)], it was confirmed that the columnar grains was Cu 3 Sn. In literature works (Li et al , 2011; Yao et al , 2018), researchers also found the Cu 3 Sn grains presented the columnar shape. It was apparent that there existed no trace of fracture happening in the interior of Cu 3 Sn grains.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…38 With the increase of the reflow time, the diffusion channel for the diffusion of Cu atoms is hindered, changing the Cu 6 Sn 5 close to the Cu substrate into Cu 3 Sn. 39 The scalloped IMCs are prone to stress concentrations that fracture the solder joint. Moreover, the free diffusion between Cu and Sn atoms can cause the overgrowth of the IMC thickness, i.e., unfavorable outcomes for their application in electronic packaging.…”
Section: Evolution Of Imcs At Thementioning
confidence: 99%